Graded layered titanium composite structures with TiB2 inclusions fabricated by selective laser melting. (1st June 2017) - Shishkovsky, Igor; Kakovkina, Nina; Sherbakov, Vladimir
Graphical abstract: Scheme for the layerwise SLM process into reinforced titanium based matrix with gradient growth by alternated of TiB2 ceramic. Highlights: Layerwise laser feasibility of titanium matrix composite (TMC) was shown. Boride-reinforced TMC and functional graded 3D samples were fabricated. Composition gradient are interesting in additive manufacturing of turbine blades. Abstract: Composite structure improvement of light-weighted metals by adding of hard ceramic particles into the metal matrix is supposed to be promising for the aerospace industry. In the present study, titanium diboride of submicron sizes were incorporated to the titanium substrate by a selective laser melting (SLM) process of Ti + (10, 15 or 20 vol%) TiB2 powder mixtures via an Ytterbium fiber laser with 1.075 mm wavelength. Optimal regimes for the 3D laser additive process were determined. We compared the changes of interfacial properties due to the difference in composition in case of the titanium matrix composites (TMC) reinforced with TiB2 . The phase analysis of the fabricated TMC showed that the initial TiB2 particles were dissolved after the remelting with different velocities. A particular attention was paid to boron dilution and secondary TiB-TiB2 phase formation mechanisms when the TiB2 was mixed with titanium. Microstructure, phase constitution and mechanical properties of the TMCs were investigated by OM, SEM, XRD and microhardness measurement. It was shown that the microstructure had two types of heterogeneity: the TiB2 particles at the interlayer interfaces and element chemical segregation on the boundaries of the tracks.